2018
DOI: 10.1038/s41375-018-0333-4
|View full text |Cite
|
Sign up to set email alerts
|

High cortactin expression in B-cell acute lymphoblastic leukemia is associated with increased transendothelial migration and bone marrow relapse

Abstract: Cancer is a major cause of death in children worldwide, with B-lineage cell acute lymphoblastic leukemia (B-ALL) being the most frequent childhood malignancy. Relapse, treatment failure and organ infiltration worsen the prognosis, warranting a better understanding of the implicated mechanisms. Cortactin is an actin-binding protein involved in cell adhesion and migration that is overexpressed in many solid tumors and in adult B-cell chronic lymphocytic leukemia. Here, we investigated cortactin expression and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 39 publications
9
18
0
1
Order By: Relevance
“…In the current study high expression of cortactin as well as its homologue HS1 was detected in B-ALL patients at diagnosis and significantly reduced after induction chemotherapy as compared to controls. These findings were in agreement with that reported by Velázquez-Avila et al, (2019), who reported higher expression of both cortactin and HS1 among B-ALL patients. Also; previous report stated that cortactin is strongly overexpressed in leukemic cell lines and primary patient-derived leukemic cells (Yin et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…In the current study high expression of cortactin as well as its homologue HS1 was detected in B-ALL patients at diagnosis and significantly reduced after induction chemotherapy as compared to controls. These findings were in agreement with that reported by Velázquez-Avila et al, (2019), who reported higher expression of both cortactin and HS1 among B-ALL patients. Also; previous report stated that cortactin is strongly overexpressed in leukemic cell lines and primary patient-derived leukemic cells (Yin et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…B-ALL, the most common type of ALL, is characterized by clonal expansion of developmentally arrested malignant B-cell precursors 2 . Approximately 20% of B-ALL patients become resistant to chemotherapy during the therapeutic process 15 .…”
Section: Discussionmentioning
confidence: 99%
“…B-cell acute lymphoblastic leukemia (B-ALL), the most common type of malignancy in children and young adults, is a genetically heterogeneous disease that derives from B cell progenitors 1 . In spite of the great advances in the treatment of B-ALL, tumor relapse in B-ALL is one of the leading causes of cancer-related death in childhood 2 . Adults with B-ALL experience even higher relapse rates, with long-term event-free survival less than 50% 3 .…”
Section: Introductionmentioning
confidence: 99%
“…CXCL12/CXCR4 axis is central in physiological hematopoietic cells development (118), but it also seems to play a role in leukemic cells neurotropism. In vitro studies revealed that astrocytes (119), choroid plexus epithelial cells (120) and meningeal cells (121) secrete CXCL12 and B-ALL blasts move toward and adhere to them (120), CXCL12 appears to promote B-ALL blasts migration across brain-CSF barrier (120,122), but possibly also across BBB (120). CCR7/CCL19 is considered essential for CNS infiltration in Notch1-induced T-ALL, but not seem to be true for other ALL types (123).…”
Section: The Role Of Adhesion Molecules In Allmentioning
confidence: 99%